PERLINDUNGAN "KHUSUS" BAGI NASABAH PERBANKAN SYARIAH DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - Ro'fah Setyowati (Masalah-Masalah Hukum, 2010)
Islamic bank existence is a fact that the umah realize the important of Islamic Law (syariah). They attempt to maximizing to apply the syariah because as consumer they need safety. If their bank apply syariah principle purerly, they will be peacefull. Therefore, a policy and effort a build syariah principle is an action to protect consumers specifically. Relating is this case, the paper will discuss about the definition of consumers protection. Besides that this paper also discuss the scope of special consumers protection. Moreover, this research to look for the rock as PPS and DSN as the main institution related to special consumers protection, fur there more, this research also to explore the problems by these institutions (DSN and DPS).Kata Kunci : Perlindungan, Nasabah, Perbankan Syariah.